QUALITY OF SELF-ORGANIZATION AS DETERMINING CONSTITUENT OF MAN OF MODEM SOCIAL STRUCTURE (Pedagogy of Higher and Secondary Education, 2022)
In the article attention is accented to that modem social structure of active transformations requires certain organizational qualities from the actors of different social roles. Existence of such qualities is the condition of support by personality of itself in a viable form in the negative terms of social cha nges and, in addition are realization of the abilities in new social projects. An author briefly opens up essence of these organizational qualities of personality and the necessity of their forming already today at teenagers by the changes in general middle and in out-of-school education becomes firmly established.
Keywords: self-organization; social structure; creative thought; intellection